Vital statistics: episcopal ordination and ordinands in England, 1646–60 - Taylor, Stephen; Fincham, Kenneth (English Historical Review, 2011)
ON 25 September 1659, the funeral of Thomas Morton, the nonagenarian bishop of Durham, took place at St Peter's Easton Maudit in Northamptonshire. The preacher praised Morton's faithful service ‘as a bishop till the very last gasp’ and cited ‘his late ordinations of priests and deacons here among you, whereof some here present received the benefit, and many more can give the testimony’.1 It is well-known that between 1646 and 1660, several bishops, including Morton, conferred holy orders in defiance of the Long Parliament's ordinance of 9 October 1646 abolishing the office and jurisdiction of bishops,2 but hitherto no one has calculated the exact numbers of ordaining bishops and ordinands or placed this activity within the context of contemporary debates over the validity of ministerial orders, so the incidence and significance of these illegal ceremonies remain unclear. Now, with the powerful assistance of the Clergy of the Church of England Database, it is possible to produce reliable figures of ordainers and ordinands, and to demonstrate a high demand for ordination which was met by bishops willing to perform the ceremony. This evidence throws important new light on the organisation, practice and popularity of episcopalianism in the late 1640s and 1650s. We shall challenge the prevalent view that the episcopate abandoned its pastoral responsibilities in the Interregnum, and suggest that the rising demand for episcopal ordination in the 1650s reveals the enduring appeal of traditional episcopalian orders in a period of proscription and intermittent persecution, at a time when the episcopate itself looked unlikely to survive for much longer.3 That ordinands were able to make contact with a diminishing number of bishops points to the effective operation of a series of semi-clandestine networks of episcopalian loyalists. Many ordinands were already serving in the state church, or else upon ordination entered the parochial ministry. This allows us to revise our understanding of the character of the clerical profession during the Interregnum. What follows falls into three sections: first, we present the evidence for ordinations in the 1640s and 1650s and analyse those bishops who were, and who were not, active ordainers; secondly, we explore the connections which allowed ordinands to be in touch with ordaining bishops; and thirdly, we investigate the motivation and careers of the ordinands themselves.
EPrint Processing Status: Full text deposited in DRO